Job rotation and multi-skilling in the semi-automated warehouse - Kleinsmith, Niela; Koene, Bas, 1966-; Gautié, Jérôme; Perez, Coralie (London : Rotterdam School of Management, Erasmus University, 2018)
With the introduction of automation and digitalized processes in the warehouse, and the dramatic growth of online shopping resulting in longer operating hours and higher product flows in warehouses, workers in the retail logistics industry are on the one hand, being squeezed out of their jobs, and on the other, being asked for ever greater flexibility in decreasingly skilled jobs with reduced wages for their efforts. Companies who have partially invested in automation technologies yet still require large amounts of manpower to operate their warehouses and are trying to find solutions for their two biggest organisational constraints: how to build flexibility into their organisation to accommodate the high variability in customer demand, and how to keep their employees' mostly repetitive, low-skilled jobs sufficiently interesting and low-strain to retain their workforce at low wages. To mitigate these two effects, logistics companies started introducing job rotation in their warehouses several years ago. However, whether employee job rotation and multi-skilling have benefitted employees remains uncertain.
Originally Published In Kleinsmith, N., Koene, B., Gautie, J., & Perez, C. (2018). Job Rotation and Multi-Skilling in the Semi-Automated Warehouse. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Job rotation; Personnel management; Warehouses -- Management